(untitled) (American Journal of Islam and Society, 2000)
This article investigates two emerging models in educational administration, namely the Christian “service-stewardship,” and the Islamic “Khilufuh.” The author traces the historical developments and intellectual traditions within which the current educational administration has evolved, and the transfoxmation that the discipline has undergone. The article highlights the basic premises, the components of each model, and the implications for educational administration. The juxtaposition of the two models reveals shared elements and divergence. The article concludes with a discussion of the potential contribution of the two models, as well as the legitimate concerns that should be addressed.